Analysis of 55 Kidd ancestry SNPs in Qatari population using ForenSeq Universal software & STRUCTURE software. Issue 1 (December 2019) - Almohammed, E.; Hadi, S.
Abstract: SNPs are good predictors of ethnicity and serval panels have been published [1 ]. The ForenSeq Signature kit (Illumina) offers coverage of 230 different markers including 55 ancestry SNPs (AISNPs). The ForenSeq Universal Analysis Software (UAS) brings the capability to analyse the sequencing data, represent results and accomplish statistical estimates of biogeographic ancestry. The ancestry prediction results in UAS are based on Principal Component Analysis (PCA) collected on several reference populations comprised in the 1000 Genomes project. This set does not include Qatari population. The data was analysed using STRUCTURE software. These data serves as an addition to the existing Middle Eastern population data for the 55 AISNPs. The Qatari population has been a melting pot of various populations and this forensic study was the first of its kind to generate new data on the genetics of Qatari population. The 55-ancestry marker allele frequency data for 150 samples were analysed and compared to 139 world populations using STRUCTURE software. FROG-kb analysis led to all Qatari samples being correctly assigned to Middle Eastern populations showing that the Illumina software needs to be enhanced by adding more databases from the Middle East. In conclusion, the results have clearly demonstrated the potential use of MPS methods to study the genetics of Qatari population.